Hubungan Tingkat Kadar Kolesterol High Density Lipoprotein dengan Kejadian Stroke Iskemik di RSUD Dr. Moewardi - Windayani, Sipkhotun, dr. Listyo Asist Pujarini, M.Sc, Sp.S, dr. D. Dewi Nirlawati (2016)
Background: Stroke was a major medical problem that caused disablement in adult age and the most frequently causing death in the world. The highest stroke mortality occurred in Indonesia, which reached 12.1 per 1,000 population. Ischemic stroke was the most common type of stroke with around 85% of stroke cases. One of the risk factors that could cause the stroke was the decreased of HDL cholesterol. HDL works to bring the cholesterol from the arteries and brought it back to heart to be disposed, therefore, the low HDL could increase the stroke risk. Purpose: The purpose of this research was to determine the relationship between HDL cholesterol levels with incidence of ischemic stroke. Method: The research method used analytic observational with cross sectional appropriate. The received data was served in tables and analyzed by used Chi-Square test in signification level α= 0.05. Result: The number of ischemic stroke patients who have low HDL cholesterol levels are 33 patients (39.3%) of 42 patients, where as in patients with no stroke mostly had normal HDL cholesterol levels are 25 patients (29.8%) of 42 patients. The results of the data analysis p value <0,001 with the value X2= 12.649 and OR= 5.392 (95% CI; 2.063 to 14.092). Conclusion: The conclusion of this research that there is a relationship between HDL cholesterol levels with incidence of ischemic stroke.